Nutrition competencies of tuck shop owners in relation to nutritional quality of products sold at Tshwane primary school tuck shops - Pretorius, Adeline (University of Pretoria, 2022)
Dissertation (MConsumer Science (Hospitality Management))--University of Pretoria, 2021.